PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KEPATUHAN PENGUNGKAPAN INVESTASI PEMERINTAH DAERAH (Studi pada Pemerintah Kabupaten/Kota di Pulau Jawa dan Sumatera) - Sri Suranta; Oktovian Siregar (Jurnal Akuntansi, 2015)
This study aims to know the effect of local government’s characteristics, which are the local government’s administrative age, the size of its investments, the number of SKPDs (working units), the educational background of the head of the local government and intergovernmental revenues, on the compliance of local government investment disclosures and compare the compliance of local government investments disclosures between local governments in Java and Sumatera. The sampling method used is purposive sampling. The study sample consists of 102 district/city governments that report the Local Government Financial Statements for Fiscal Year 2013 and have been audited by the Indonesia’s Supreme Audit Board in 2014. This study uses multiple regression analysis and t-test procedure and also does the classical assumptions test including normality, autocorrelation, heteroscedasticity, and multicollinearity test using Statistical Package for the Social Sciences (SPSS). The results show that the local government’s administrative age has significant effect on the disclosure of local government investments, while the size of its investments, the number of SKPDs (working units), the educational background of the head of the local government and intergovernmental revenues have no significant effect on the disclosure of local government investments. Keywords: local government investment disclosures, local government financial statements, organizational theory, characteristics of an organization.